Toripalimab Plus Chemotherapy for Patients With Treatment-Naive Advanced Non–Small-Cell Lung Cancer: A Multicenter Randomized Phase III Trial (CHOICE-01). Issue 3 (7th October 2022) - Wang, Zhijie; Wu, Lin; Li, Baolan; Cheng, Ying; Li, Xiaoling; Wang, Xicheng; Han, Liang; Wu, Xiaohong; Fan, Yun; Yu, Yan; Lv, Dongqing; Shi, Jianhua; et al.
Abstract : PURPOSE: The CHOICE-01 study investigated the efficacy and safety of toripalimab in combination with chemotherapy as a first-line treatment for advanced non–small-cell lung cancer (NSCLC). PATIENTS AND METHODS: Patients (N = 465) with treatment-naive, advanced NSCLC without EGFR/ALK mutations were randomly assigned 2:1 to receive toripalimab 240 mg (n = 309) or placebo (n = 156) once every 3 weeks in combination with chemotherapy for 4-6 cycles, followed by the maintenance of toripalimab or placebo once every 3 weeks plus standard care. Stratification factors included programmed death ligand-1 expression status, histology, and smoking status. The primary end point was progression-free survival (PFS) by investigator per RECIST v1.1. Secondary end points included overall survival and safety. RESULTS: At the final PFS analysis, PFS was significantly longer in the toripalimab arm than in the placebo arm (median PFS, 8.4 v 5.6 months, hazard ratio = 0.49; 95% CI, 0.39 to 0.61; two-sided P < .0001). At the interim OS analysis, the toripalimab arm had a significantly longer OS than the placebo arm (median OS not reached v 17.1 months, hazard ratio = 0.69; 95% CI, 0.53 to 0.92; two-sided P = .0099). The incidence of grade ≥ 3 adverse events was similar between the two arms. Treatment effects were similar regardless of programmed death ligand-1 status. Genomic analysis using whole-exome sequencing from 394 available tumor samples revealed that patients with high tumor mutational burden were associated with significantly better PFS in the toripalimab arm (median PFS 13.1 v 5.5 months, interaction P = .026). Notably, patients with mutations in the focal adhesion-PI3K-Akt signaling pathway achieved significantly better PFS and OS in the toripalimab arm (interaction P values ≤ .001). CONCLUSION: Toripalimab plus chemotherapy significantly improves PFS and OS in patients with treatment-naive advanced NSCLC while having a manageable safety profile. Subgroup analysis showed the OS benefit was mainly driven by the nonsquamous subpopulation.